(untitled) (Fiep Bulletin - online, 2015)
The children motor development is an area of study with few quantitative researches. More specifically, most of the studies in that area are of the descriptive type, with the objective of identifying patterns of motor skills executed by children. Considering that the jump is a complex task and present in the daily activities of the children, the objective of this study was to do a biomechanical analysis of the children’s long jump considering their phases of motor development, according to the matrix proposed by Gallahue. For this exploratory descriptive study 9 children’s long jump with age between 5 and 12 years of the municipal net of teaching of the city of Florianópolis SC were analyzed. After the approval of the Committee of Ethics in Research of UDESC the collections of data were accomplished at the Laboratory of Biomechanics of UDESC, being used a platform of force AMTI-OR6-5 to calibrated to a frequency of sampling of 900 Hz, a camera of the Peak Motus t System 60 Hz, and the matrix for qualitative analysis of the long jump proposed by Gallahue, that allows to classify the performer in three phases of motor development: initial, elementary and mature. It was analyzed the angular variables (angle of the log and knee), kinetic variables (peak of force, impulse rate), time of execution of the jump and reached distance. The results of the study demonstrate that some variables can be extremely important for the differentiation of the development phases. The angles of the trunk and knee can indicate differences among the development phases and could be used in a quantitative classification of these children. Among the kinetic variables the impulse rate can be mentioned in Y and X, that had larger values according to the evolution of the development phases. The distance reached in the mature phase was larger than those in the elementary and initial phases, could indicate relationship between the development phase and the performance of the jump. With this study it can be concluded that the analysis of biomechanics parameters can be used in the classification of the phases of children’s motor development, and that quantitative values could help the qualitative analysis proposed by the model of Gallahue.